Vitellogenin receptor transports the 30K protein LP1 without cell-penetrating peptide, into the oocytes of the silkworm, Bombyx mori - Xu, Yinying; Shen, Guanwang; Wu, Jinxin; Mao, Xueqin; Jia, Linbang; Zhang, Yan; Xia, Qingyou; Lin, Ying (Frontiers in Physiology, 2023)
Vitellogenin receptors (VgRs) transport vitellogenin (Vg) into oocytes, thereby promoting egg growth and embryonic development. VgRs recognize and transport multiple ligands in oviparous animals, but their role in insects is rarely reported. In this study, we investigated whether Bombyx mori VgR (BmVgR) binds and transports lipoprotein-1 (BmLP1) and lipoprotein-7 (BmLP7) of the 30kDa lipoproteins (30K proteins), which are essential for egg formation and embryonic development in B. mori. Protein sequence analysis showed BmLP7, similar to reported lipoprotein-3 (BmLP3), contains the cell-penetrating peptides and Cysteine position, while BmLP1 has not. Assays using Spodoptera frugiperda ovary cells (sf9) indicated the direct entry of BmLP7 into the cells, whereas BmLP1 failed to enter. However, co-immunoprecipitation (Co-IP) assays indicated that BmVgR could bind BmLP1. Western blotting and immunofluorescence assays further revealed that over-expressed BmVgR could transport BmLP1 into sf9 cells. Co-IP assays showed that SE11C (comprising LBD1+EGF1+OTC domains of BmVgR) or SE22C (comprising LBD2+EGF2+OTC domains of BmVgR) could bind BmLP1. Over-expressed SE11C or SE22C could also transport BmLP1 into sf9 cells. Western blotting revealed that the ability of SE11C to transport BmLP1 might be stronger than that of SE22C. In the vit mutant with BmVgR gene mutation (vit/vit), SDS-PAGE and western blotting showed the content of BmLP1 in the ovary, like BmVg, was lower than that in the normal silkworm. When transgenic with hsp70 promoter over-expressed BmVgR in the vit mutant, we found that the phenotype of the vit mutant was partly rescued after heat treatment. And contents of BmLP1 and BmVg in vit mutant over-expressed BmVgR were higher than in the vit mutant. We conclude that BmVgR and its two repeat domains could bind and transport BmLP1 into the oocytes of the silkworm, besides BmVg. These results will provide a reference for studying the molecular mechanism of VgR transporting ligands in insects.